Left pneumonectomy and middle lobectomy for bronchiectasis - Kürklü, E. U. (1973)
Kürklü, E. U., and le Roux, B. T. (1973). Thorax, 28, 535-536. Left pneumonectomy and middle lobectomy for bronchiectasis. Left pneumonectomy and middle lobectomy were undertaken in a child for bilateral bronchiectasis of this extent. The thoracic surgeon who works among a large community medically ill served and among whom respiratory disease is common is frequently called upon to manage bronchiectasis surgically.